PENGEMBANGAN MEDIA PEMBELAJARAN “UMA LENGGE” UNTUK MENINGKATKAN KREATIVITAS PEMBELAJARAN SENI RUPA SISWA KELAS V SDN RISA - Indah Purnama Sari; A Gaffar Hidayat; Putri Febrianty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning media based on the traditional house of Uma Lengge to enhance students’ creativity in visual arts learning for fifth-grade students at SDN Risa. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The trial subjects were 17 fifth-grade students. Data were collected through pretest and posttest, as well as student response questionnaires. The results indicated an increase in the average score from 49.1 in the pretest to 80.2 in the posttest, with a difference of 31.1 points, indicating the effectiveness of the media. Student responses to the media achieved an average score of 3.76 (“Very Good” category), showing that this media is attractive, easy to use, and encourages active engagement in learning. The Uma Lengge media not only helps students understand visual arts material more concretely but also strengthens the connection between learning and local culture, creating a contextual and meaningful learning experience. This study recommends the use of local wisdom-based media as an innovative alternative in visual arts learning in elementary schools.